Completion and Antithesis in Piano Sonata No. 6 by S.C. Eckhardt-Gramatté - Colton, Glenn (Canadian University Music Review / Revue de musique des universités canadiennes, 1997)
The Piano Sonata no. 6 by S.C. Eckhardt-Gramatté evolved as a composite work spanning two distinct phases of the composer's career. The first movement (1928), for left hand alone, is representative of the neo-romanticism of her early works, while the atonal second movement (1952), for right hand, typifies the composer's later style. As a synthesis of the first two movements, the finale re-interprets these conflicting tonal and stylistic paradigms, contextually transforming the preceding movements and imbuing each with new meaning. This process is closely analogous to a concept Harold Bloom describes in poetic terms as tessera, or "completion and antithesis."